Training and organizational commitment - Ismail, Hussein Nabil (2015)
In this study, we investigated the impact of organizational training on organizational commitment and whether goal orientation moderates the relationship between training and commitment. The sample consisted of 124 employees from different industries in the country of Lebanon. Multiple regression and hierarchical moderated regression were used to test hypotheses. The results of the analysis showed that training has a significant effect on organizational commitment. Moderation analysis showed that the relationship between training and affective commitment was stronger for individuals who had higher levels of learning goal orientation. Performance goal orientation failed to moderate the relationship between training and affective commitment. Ultimately, this suggests that advanced training offered to individuals with performance goal orientations may not necessarily increase their commitment to their employer, in contrast to individuals with learning goal orientations. Theoretical and management implications in the context of Lebanon are proposed.